Dynamic Changes in the Global Transcriptome and MicroRNAome Reveal Complex miRNA-mRNA Regulation in Early Stages of the Bi-Directional Development of Echinococcus granulosus Protoscoleces - Bai, Yun; Zhang, Zhuangzhi; Jin, Lei; Zhu, Yongqiang; Zhao, Li; Shi, Baoxin; Li, Jun; Guo, Gang; Guo, Baoping; McManus, Donald P.; Wang, Shengyue; Zhang, Wenbao (Frontiers in Microbiology, 2020)
Background Cystic echinococcosis is a life-threatening disease caused by the larval stages of the dog tapeworm Echinococcus granulosus. Protoscoleces (PSCs) of this worm have the ability of bi-directional development to either larval cysts or strobilar adult worms. However, the molecular mechanisms underlying this development process are unknown. Results RNA and small RNAs sequencing was employed to characterize the gene and miRNA expression at 0–24 h and 7–14 days in the bi-directional development of PSCs. A total of 963 genes and 31 miRNAs were differentially expressed in the early development of PSCs to adult worms whereas 972 genes and 27 miRNAs were differentially expressed in the early development of PSCs to cysts. Pairwise comparison between the two developmental patterns showed that 172 genes and 15 miRNAs were differentially expressed at three time-points. Most of these genes were temporally changed at 24 h or 7 days. GO enrichment analysis revealed that the differentially expressed genes in early adult worm development are associated with nervous system development and carbohydrate metabolic process; whereas, the differentially expressed genes in early cystic development are associated with transmembrane transporter activity and nucleoside triphosphatase activity. In addition, miR-71 and miR-219 regulated genes are likely involved in oxidation reduction in adult worm development. Conclusion The early stages of bi-directional development in E. granulosus PSCs are controlled by miRNAs and genes likely associated with nervous system development and carbohydrate metabolic process. ATP-dependent transporter genes are associated with cystic development. These results may be important for exploring the mechanisms underlying early development in E. granulosus providing novel information that can be used to discover new therapeutics for controlling cystic echinococcosis.